The role of ethnic minorities in the Croatian economy until 1945 - Kolar-Dimitrijević , Mira (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the importance of ethnic minorities for Croatia’s economic development from the eighteenth century until the end of the Second World War. The aim of the study is to demonstrate the impact of migration and the country’s multiethnic character on the development of trade, industry, finance, and infrastructure. The author employs a historical-economic method using statistical data, historical studies, and examples of the activities of individual national groups. The research shows that Croatia’s location along important communication routes encouraged the settlement of Serbs, Germans, Czechs, Slovaks, Jews, Greeks, and Aromanians (Cincars). These communities played a significant role in the development of entrepreneurship, banking, craftsmanship, and commerce. The ports of Rijeka and Trieste were of particular importance, becoming centers of economic activity and international contacts. The author emphasizes that most Croats remained connected with agriculture and administration, whereas capital and modernization initiatives were often in the hands of minority representatives. The conclusions indicate that Croatia’s economic development was to a large extent the result of cooperation among different ethnic groups and that the country’s multicultural character facilitated modernization processes and integration into the European economy.